Relationship between self-efficacy and learning motivation towards the acceptance of E-Learning among TVET students - M Asojan, Lohanya; Omar, Muhd Khaizer (Human Resources Management Academic Research Society (HRMARS), 2024)
In response to the global shift towards digital transformation in education, the Malaysian education system has witnessed a significant transition from traditional face-to-face learning to the integration of 21st-century education principles. The COVID-19 pandemic further accelerated this shift, causing unprecedented disruptions and prompting the adoption of ELearning platforms in educational institutions. While e-learning offers flexibility and accessibility, its acceptance among students, particularly in Technical and Vocational Education and Training (TVET) institutes such as community colleges, polytechnics, and other private institutes, remains a topic of consideration. Hence, this study focuses on understanding the relationship between students' acceptance of E-Learning, with a specific emphasis on self-efficacy. This quantitative survey involved 155 students from several TVET Institutions in Kajang, Malaysia. The instrument were adapted from (Latip et al., 2020; Panergayo et al., 2022). The study reveals a statistically significant correlation between motivation and the acceptance of E-Learning, with a p-value less than 0.001. The high positive effect size coefficient (0.828) suggests a strong association between motivation and ELearning acceptance. These insights can inform educational policies and practices aimed at promoting a positive and supportive learning environment for E-Learning adoption in technical and vocational education. As the demand for E-Learning continues to rise globally, understanding the dynamics at play within the Malaysian context will contribute valuable knowledge to education policymakers, institutions, and practitioners.